CLINICAL ASPECTS OF PATIENTS WITH NON-REMOVABLE PROSTHESIS RESULTS OF ZRO2 COATED PROSTHESES - O.M. Yakovyn; Z.R. Ozhohan (Український стоматологічний альманах)
The clinical aspects of prosthetic patients with dentition defects of different types of orthopedic designs are reproduced in the article. The aim of our research is to improve the treatment of patients with orthopedic defects dentition using aesthetic fixed prosthetic appliances by improving their manufacturing stages and grounding of the proposed treatment methods. The objects of our study are patients who have orthopedic constructions made of dental alloys of non-precious (basic) metals. Groups include 100 patients of age 20-55 years, where existing orthopedic constructions are made of dental alloys of non-precious (basic) metals, as well as control group of patients for who orthopedic constructions based on zirconium dioxide is made.